Pembelajaran Rangkaian Listrik dengan Aplikasi TinkerCAD Circuit pada Akademisi di Indonesia - Ratnadewi, Ratnadewi; Muliady, Muliady; Prijono, Agus; Susanthi, Yohana; Sunoto, Tio Dewantho; Chandra, Eric; Setiawan, Aldi; Ananda, Rio (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
The development of the world of education that increasingly prioritizes asynchronous learning encourages more platforms and applications to be launched online learning by combining knowledge and skills. However, there are still obstacles when students/teachers first try to use the application/platform self-taught. In order to bridge this gap, the UKM TE Study Program held a service by providing simulation and coding workshops on electrical circuits with the TinkerCAD Circuit web-based application for students and teachers in junior high schools. The main purpose of this PkM is to be a motivation and basis for participants to learn electrical circuits, and it can even be used as an online learning option in schools.